Corporate governance: SMES experience in Metro Cebu, Philippines / Challoner A. Matero and Marie Jane J. Matero - Challoner, A. Matero; Marie Jane, J. Matero (2010)
The paper is based on the study on the perception and practices of SMEs in Metro Cebu on corporate governance, and tested a theory that size, company specifics, and corporate governance practices influenced compliance with the Code of Corporate Governance. The problem was answered with a descriptive research and inferential design utilizing convenience sampling of 30 SMEs-board members using questionnaire, interview, and analysis of audited financial statements.Perception on corporate governance of SMEs in Metro Cebu highly complied with the Code of Corporate Governance. However, practices on corporate governance disclosed gaps such as no independent board, no formalized written code of conduct, pre-audit task of internal auditor, and high debt ratio. Code emphasis on board governance, supply of information, accountability and audit, stockholders' rights and protection of minority stockholders, evaluation systems, disclosure and transparency, and commitment to corporate governance differ significantly between SMEs. The theory was confirmed that size, company specifics, and corporate governance practices influenced compliance with the Code of Corporate Governance. Recommendations were offered to help SMEs champion corporate governance. A Code of Corporate Governance for SMEs must be developed; setting-up corporate governance structure should consider the size of assets of SMEs as well as the costs and benefits; Securities and Exchange Commission, in coordination with industry associations, shall initiate orientation requirement of new BODs, continuing education of current BODs, dissemination of corporate governance as a topic in all business-related courses and as an elective in non-business courses.